Impact of Environmental Toxicants on Testicular Function - Mathur, P. P.; Saradha, B.; Vaithinathan, S. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
In recent years, the impact of various environmental toxicants on male reproductive function has received considerable attention, partly fuelled by the reports of falling sperm count and rising reproductive disorders in human population. Environmental toxicants disturb the pro-oxidant/ anti-oxidant balance of the testis resulting in impairment of testicular function. The reactive oxygen species (ROS) and associated oxidative stress has grown up to the point of molecular mechanism responsible for male infertility. Therefore, there is a greater need to look into the reason behind the vulnerability of male reproductive system to ROS. Under physiological conditions, the testicular spermatogenesis and steroidogenesis are associated with production of ROS that makes them more susceptible to oxidative stress. In addition, exposure to toxicants aggravates the production of ROS to greater extent. ROS are involved in regulation of testicular functions within critical levels. The present review outlines the source of ROS, its role in testis and summarizes recent studies on ROSmediated effects of environmental toxicants on testicular function. Testicular spermatogenesis and steroidogenesis are a source of ROS and also a target for their disruptive actions. The role of environmental toxicants in changing testicular ROS levels merits further investigation.
Keywords: spermatogenesis